Understanding creativity process through electroencephalography measurement on creativity-related cognitive factors - Yin, Yuan; Wang, Pan; Childs, Peter R. N. (Frontiers in Neuroscience, 2022)
Neurotechnology approaches, such as electroencephalography (EEG), can aid understanding of the cognitive processes behind creativity. To identify and compare the EEG characteristics of creativity-related cognitive factors (remote association, common association, combination, recall and retrieval), 30 participants were recruited to conduct an EEG induction study. From the event-related potential (ERP) results and spectral analysis, the study supports that creativity is related to the frontal lobe areas of the brain and common association is an unconscious process. The results help explain why some creativity-related cognitive factors are involved either more or less readily than others in the creative design process from workload aspects. This study identifies the part of the brain that is involved in the combination cognitive factor and detects the ERP results on cognitive factors. This study can be used by designers and researchers to further understand the cognitive processes of creativity.